2013
DOI: 10.4103/1319-2442.113855
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alfa and monocyte chemoattractant protein-1 gene polymorphisms in kidney transplant recipients

Abstract: Tumor necrosis factor-alfa (TNF-α) gene polymorphism is supposed to have a significant influence on the incidence of acute rejection in renal transplantation. The monocyte chemoattractant protein-1 (MCP-1) is another factor supposed to modulate graft rejection. We studied TNF-α and MCP-1 gene polymorphisms in 84 kidney allograft recipients with polymerase chain reaction and restriction fragment length polymorphism and their serum levels by enzyme-linked immunosorbent assay. The patients were classified into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The promoter region of the MCP-1 gene ( MCP1 ) was shown to influence MCP-1 expression [13,14]. The MCP1- 2518G allele was associated with up-regulation of both MCP-1 transcript and protein levels in many studies [11,1316], but not all [17]. HD subjects with AG+GG genotypes of the MCP-1 gene ( MCP1 rs1024611) had higher MCP-1 levels than those with the AA variant [11]; this may predispose HD patients to HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The promoter region of the MCP-1 gene ( MCP1 ) was shown to influence MCP-1 expression [13,14]. The MCP1- 2518G allele was associated with up-regulation of both MCP-1 transcript and protein levels in many studies [11,1316], but not all [17]. HD subjects with AG+GG genotypes of the MCP-1 gene ( MCP1 rs1024611) had higher MCP-1 levels than those with the AA variant [11]; this may predispose HD patients to HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor Necrosis Factor-a (TNF-a) is an endotoxin-induced glycoprotein, originally described as a circulating factor that can cause necrosis of tumor. However, accumulating evidence demonstrated that TNF-a is a key regulator of the inflammatory response and is implicated in the pathophysiological course of multiple disorders [14,15]. TNF-a, along with other pro-inflammatory cytokines (e.g., IL-6), are elevated in patients undergoing hemodialysis (HD).…”
Section: Discussionmentioning
confidence: 99%
“…In allograft rejection, activated immune cells involving macrophages, CD4+ T cells, natural killer (NK) cells, neutrophils, and endothelial cells have been shown to produce exaggerated amounts of TNF-a. Of note, combined serial assays of serum TNF-a and serum creatinine have greater predictive value than either test alone for the early diagnosis of acute rejection [2,14,15], while TNF-a gene polymorphisms may reveal a subgroup of graft recipients under an elevated risk of acute and delayed rejection [4]. Intriguingly, high TNF-a levels in donors may confer an additional risk for delayed graft rejection in kidney recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation